2020
DOI: 10.15252/embr.202050421
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A viruses limit NLRP3‐NEK7‐complex formation and pyroptosis in human macrophages

Abstract: Pyroptosis is a fulminant form of macrophage cell death, contributing to release of pro-inflammatory cytokines. In humans, it depends on caspase 1/4-activation of gasdermin D and is characterized by the release of cytoplasmic content. Pathogens apply strategies to avoid or antagonize this host response. We demonstrate here that a small accessory protein (PB1-F2) of contemporary H5N1 and H3N2 influenza A viruses (IAV) curtails fulminant cell death of infected human macrophages. Infection of macrophages with a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 98 publications
0
20
0
1
Order By: Relevance
“…These differences in cellular compartmentalization could explain the opposite effects observed. Accordingly, the pro-apoptotic effects exerted by PB1-F2 on macrophages has recently been called into question [ 26 ]. Similarly, the pro-inflammatory activity of PB1-F2 is highly questioned, as it has also been described that PB1-F2 is able to inhibit the host response, especially through its inhibitory action on MAVS [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…These differences in cellular compartmentalization could explain the opposite effects observed. Accordingly, the pro-apoptotic effects exerted by PB1-F2 on macrophages has recently been called into question [ 26 ]. Similarly, the pro-inflammatory activity of PB1-F2 is highly questioned, as it has also been described that PB1-F2 is able to inhibit the host response, especially through its inhibitory action on MAVS [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…NIMA-related kinase 7 (NEK7) is widely expressed in the brain, which is related to the initiation of mitosis, cell cycle progression, and mitotic progression [ 28 ]. Studies have found that NEK7 regulated the activation of NLRP3, which played an important role in the inflammatory cascade of macrophages [ 29 ]. Here, we show that liquiritin (40 mg/kg) inhibited the protein expression of NLRP3 inflammasome components in the hippocampal region by western blot and IHC assay, accompanied by significantly lower levels of IL-1 β and IL-18 as well.…”
Section: Discussionmentioning
confidence: 99%
“…A study suggested that LRR domain is unnecessary for mouse NLRP3 inflammasome activation [37]. However, most of viruses use the viral proteins to interact with the LRR domain to activate/promote NLRP3 inflammasome, such as EV71 3D interacted with LRR domain of NLRP3 [28]; Zika virus NS5 protein binds NLRP3 by interacting with NACHT and LRR domains [29]; and PB1-F2 of Influenza A viruses binds to the PYD and LRR domain of NLRP3 [38], so we speculated that LRR domain may act as the NLRP3 receptor domain for ligands after viral infection. Without stimulator, NLRP3 protein is thought to be auto-repressed through interaction between the domains of NACHT and LRRs.…”
Section: Discussionmentioning
confidence: 99%